Pengaruh Bantuan Modal Usaha, Pendampingan, dan Penggunaan Digital Marketing Terhadap Pendapatan UMKM Binaan LAZ DASI NTB - Putranto, Eko Sigit; Nasir, Mohamad Abdun; Sanurdi, Sanurdi; Amini, Titik Husnawati (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2025)
An organization that serves as a strategic partner for MSMEs in their endeavors to enhance economic welfare and promote sustainable company growth is required in order to boost MSMEs' revenue and get beyond a number of challenges (barriers) encountered in the industry. The challenge of funding Micro, Small, and Medium-Sized Businesses supported by the West Nusa Tenggara Zakat Institution is what spurred this study. The quality of human resources is actually poor, and a lack of business acumen and proficiency with digital marketing technologies leads to lower productivity. The study's goal was to ascertain if the income of micro, small, and medium-sized businesses (Y) supported by the West Nusa Tenggara Zakat Institution might be impacted by business capital assistance (X1), mentoring (X2), and the use of digital marketing (X3). Association for Zakat in West Nusa Tenggara. This research is a quantitative survey quantitative. 60 respondents made up the whole sample, which was selected using the Cluster Area Sampling approach. sampling of an area. The Slovin formula is used by the author to determine the number of samples with a big population. Interviews with several micro, small, and medium company players reinforce the data gathered via survey distribution and analysis using SPSS software version 25. The study's findings show that the West Nusa Tenggara Zakat Dasi Institution's support of micro, small, and medium-sized enterprises is significantly impacted by mentorship, business capital assistance, and the use of digital marketing. While the revenue of micro, small, and medium-sized enterprises is not significantly affected by the usage of digital marketing, these firms do benefit from business capital support and coaching. As a result, H3 is rejected while H1, H2, and H4 are allowed.